2013
DOI: 10.1021/nl400258t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of MoS2 and MoSe2 Films with Vertically Aligned Layers

Abstract: Layered materials consist of molecular layers stacked together by weak interlayer interactions. They often crystallize to form atomically smooth thin films, nanotubes, and platelet or fullerene-like nanoparticles due to the anisotropic bonding. Structures that predominately expose edges of the layers exhibit high surface energy and are often considered unstable. In this communication, we present a synthesis process to grow MoS2 and MoSe2 thin films with vertically aligned layers, thereby maximally exposing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

117
1,771
6
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,122 publications
(1,934 citation statements)
references
References 65 publications
117
1,771
6
6
Order By: Relevance
“…The distance between the two peaks in the line intensity profile shown in the bottom of Figure 2e is ≈0.307 nm, which matches well with the value of the unit cell parameter of MoS 2 39. 2D materials with high‐quality vertically oriented few‐layer structures have been reported to be ideal materials for photodetectors, energy storage, catalysis, and edge emitter devices because of their high active surface areas, strong light absorptions, and quick longitudinal intralayer transport speeds 34, 35, 36, 37, 40, 41, 42. Therefore, these V‐MoS 2 nanosheets may also have great potential applications in multifarious fields.…”
Section: Experimental and Characterizationsupporting
confidence: 73%
See 1 more Smart Citation
“…The distance between the two peaks in the line intensity profile shown in the bottom of Figure 2e is ≈0.307 nm, which matches well with the value of the unit cell parameter of MoS 2 39. 2D materials with high‐quality vertically oriented few‐layer structures have been reported to be ideal materials for photodetectors, energy storage, catalysis, and edge emitter devices because of their high active surface areas, strong light absorptions, and quick longitudinal intralayer transport speeds 34, 35, 36, 37, 40, 41, 42. Therefore, these V‐MoS 2 nanosheets may also have great potential applications in multifarious fields.…”
Section: Experimental and Characterizationsupporting
confidence: 73%
“…Therefore, the response time of PSD may be longer than that of the photodetector as transverse carrier transport is also needed in LPE for PSD based on longitudinal transport. Moreover, though it is usually suggested that the intralayer transport speed of photogenerated carriers is much larger than the interlayer speed,33, 34, 41 the quantitative difference between them is still unknown experimentally because of the single longitudinal transport process in the MoS 2 ‐based photodetector, from which only the interlayer (parallel‐oriented layered structure) or intralayer (vertically oriented layered structure) transport time can be obtained. However, using the response speed of the PSD may be a good method to extract both the interlayer and the intralayer transport speeds simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…e) Verticle aligned MoS 2 structures. Reproduced with permission 51. Copyritht 2013, American Chemical Society.…”
Section: Edges As Active Sitesmentioning
confidence: 99%
“…Vertical aligned MoS 2 layers grown on electrode would maximally expose edges as well as increasing the conductivity, although they are not easy to fabricate. The edges are thermodynamically unfavorable with basal plane by 2 orders of magnitude of surface energy, the vertical aligned structure could still be formed through a kinetically controlled rapid growth method (Figure 2e) 51. In the chemical vapor deposition MoS 2 synthesis, chemical conversion is a fast step comparing with gas diffusion, if diffusion along the layers through basal plane is much faster than diffusion across layers, then vertical growth is favored.…”
Section: Edges As Active Sitesmentioning
confidence: 99%
“…Extensive efforts have been made to improve the HER activities of MoS 2 ‐based catalysts in acidic media by strategies such as nanostructure engineering,35, 36, 37, 38 defect engineering,39, 40, 41, 42, 43 phase engineering,44, 45, 46, 47, 48 and heteroatom doping49, 50, 51 to increase the number or enhance the intrinsic activity of active sites. However, little work has been reported to improve the HER activities of MoS 2 ‐based materials in alkaline media 31, 52.…”
Section: Introductionmentioning
confidence: 99%